2020
DOI: 10.3847/1538-4357/ab5f61
|View full text |Cite
|
Sign up to set email alerts
|

Model-independent Estimations for the Cosmic Curvature from the Latest Strong Gravitational Lensing Systems

Abstract: Model-independent measurements for the cosmic spatial curvature, which is related to the nature of cosmic space-time geometry, plays an important role in cosmology. On the basis of the Distance Sum Rule in the Friedmann-Lemaître-Robertson-Walker metric, (distance ratio) measurements of strong gravitational lensing (SGL) systems together with distances from type Ia supernovae observations have been proposed to directly estimate the spatial curvature without any assumptions for the theories of gravity and conten… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 106 publications
4
22
0
Order By: Relevance
“…The precision of this estimate is comparable to the recent analysis of Cao et al [10], which represented the precision of ΔΩ k ∼ 10 −2 with 250 well-observed radio quasars. Such conclusion is also well consistent with the cosmic curvature derived from the strong lensing and supernova distance measurements in the framework of another model-independent test based on the distance sum rule [15].…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The precision of this estimate is comparable to the recent analysis of Cao et al [10], which represented the precision of ΔΩ k ∼ 10 −2 with 250 well-observed radio quasars. Such conclusion is also well consistent with the cosmic curvature derived from the strong lensing and supernova distance measurements in the framework of another model-independent test based on the distance sum rule [15].…”
Section: Resultssupporting
confidence: 87%
“…In other words the expected precision is ΔΩ k = 10 −2 with the DECIGO+CC and ΔΩ k = 10 −1 with the ET+CC. Compared to the latest model-independent estimations of the spatial curvature using the distance sum rule method [15], our results suggest a considerable improvement in precision when the future GW observatories provide rich statistics of D L (z) measurements. In order to surpass the limitations of small CC sample we reconstructed H (z) function using GP technique and used it together with reconstructed D L (z) and D L (z) to investigate Ω k (z).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…There are always differences between the lensing redshifts and the nearest quasars. This issue can be overcame by reconstructing a continuous distance function that best approximates the discrete observed data using a polynomial fit (Räsänen et al 2015;Liao et al 2017;Li et al 2018a;Collett et al 2019;Liao 2019;Zhou & Li 2020). In our analysis, we construct the dimensionless distance function d(z) in a cosmology independent way by fitting a third-order polynomial with initial conditions d(0) = 0 and d ′ (0) = 1, to the quasar data.…”
Section: Strong Lensing Data: Time-delay Distance Ratiosmentioning
confidence: 99%
“…Furthermore, the comparision of the inferred values of the cosmic curvature from two or more lens-source pairs provides a consistency test of the FLRW metric (Räsänen et al 2015). Based on the sum rule of distances along null geodesics of the FLRW metric, modelindependent determinations of the spatial curvature have been implemented by combining strong gravitational lensing systems with other distance indicators, including SNe Ia (Räsänen et al 2015;Liao et al 2017Liao et al , 2019Liao et al , 2020Xia et al 2017;Denissenya et al 2018;Li et al 2018a;Collett et al 2019;Zhou & Li 2020), gravitational waves (GWs; Liao 2019), and compact radio sources (Qi et al 2019b). Such model-independent curvature determinations have also been proposed using future time delay measurements of strongly lensed transients (such as fast radio bursts, GWs, and SNe) and luminosity distances of SNe Ia (Li et al 2018b(Li et al , 2019Qi et al 2019a).…”
Section: Introductionmentioning
confidence: 99%